A atividade física como conteúdo do lazer ativo para promoção de saúde - Volpe, Alessandra Márcia Montanhini (2015)
This dissertation consists of two papers of literature review. Both with the goal to analyze the practice of active leisure, associated with physical activity and health promotion. For the first item, the same discourse genre and textbooks were selected that focused on leisure, quality of life and health promotion, in order to verify the relationship between leisure, physical activity and quality of life. The second article consists of an integrative literature review, research published containing the following key words "health promotion" and "leisure" and "physical activity". In the period between January 2010 to December 2014 in the PubMed database. Analyses of selected articles revealed a significant positive effect of physical activity during leisure time. Anyway, it is clear that, in both studies, active recreation, when aggregate à physical activity is an important element in the context of health promotion.